Pengaruh Pupuk NPK dan Klon Terhadap Pertumbuhan Bibit Kakao (Theobrama Cacao L) - Junenti Junenti; Nikmah Nikmah; Linda Bachrun (Agrisia: Jurnal Ilmu-Ilmu Pertanian, 2023)
Study aims to determine the growth response of cocoa seedlings (Theobroma cacaoL) to NPK fertilizer treatment. The research was conducted on the land of the Cangkring Indah Farmer Women Group, Kampung Cangkring, Jayalaksana Village, Cabang bungin District, Bekasi Regency in August 2021 to November 2021. The experimental designused was Factorial Randomized Group Design (RAK) with 3 replications. The first factor is NPK fertilizer consisting of five levels of 0 grams (N0), 5 grams (N1), 10 grams (N2), 15 grams (N3), and 20 grams per plant (N4) per plant, the second factor is cocoa clones consisting of three clones, namely MCC 1 (K1), SUL 1(K2), and SUL 2 (K3). Eachtreatment has 3 sample plants resulting in combinations with a total of 135 sample plants. The results of the comparison test between treatmens in the of NPK fertilizer 0 gr/plant or control (N0K2), had a significant ef ects on plant height at the age of 2, 4, and6weeks after planting, and in the treament NPK fertilizer 10 gr/plant (N2K2) hadasignificant ef ects on the number of leaves at the of 6 and 8 weeks after planting